Crystallinity of Raw Rice Starch Granules As Indexed By Corrosion with Hydrochloric Acid and Amylase - Juliano, Bienvenido O.; Perez, C.M. (Wiley, 1990)
After 15 d in 2.2N HCl at 35°C, residual starch of 34 granular rice starches differing in apparent amylose content (AC) and final gelatinization temperature (GT) ranged from 1.3 to 20.8% and was verified to correlate significantly with GT (r = 0.69**) and AC (r = 0.44**). Residual starch after 5 h corrosion with crude Chalara paradoxa amylase ranged from 0 to 29.4% and also correlated significantly with GT (r = 0.45**) and AC (r = 0.70**). The amounts of residual starch after Lintnerization and after C. paradoxa amylase digestion were significantly correlated (r = 0.72**).